Discovery of Ezrin Expression as a Potential Biomarker for Chemically Induced Ocular Irritation Using Human Corneal Epithelium Cell Line and a Reconstructed Human Cornea-like Epithelium Model. (8th June 2018) - Ye, Dong-Jin; Kwon, Yeo-Jung; Baek, Hyoung-Seok; Shin, Sangyun; Lee, Choongho; Yun, Jun-Won; Nam, Ki Taek; Lim, Kyung-Min; Chun, Young-Jin
Abstract: Numerous studies have attempted to develop a new in vitro eye irritation test (EIT). To obtain more reliable results from EIT, potential new biomarkers that reflect eye irritation by chemicals must be identified. We investigated candidate biomarkers for eye irritation, using a proteomics approach. Sodium lauryl sulfate (SLS) or benzalkonium chloride (BAC) was applied on a reconstructed human cornea-like epithelium model, MCTT HCE, and corneal protein expression was examined by two-dimensional gel electrophoresis. We found that ezrin ( EZR ) was significantly upregulated by SLS or BAC. In addition, upregulation of EZR in immortalized human corneal cells treated with SLS or BAC was confirmed by quantitative reverse transcription-PCR and western blot analysis. Furthermore, other well-known eye irritants such as cetylpyridinium bromide, Triton X-100, cyclohexanol, ethanol, 2-methyl-1-pentanol, and sodium hydroxide significantly increased EZR expression in immortalized human corneal cells. Induction of EZR promoter activity in irritant-treated human corneal cells was confirmed by a luciferase gene reporter assay. In conclusion, EZR expression may be a potential biomarker for detecting eye irritation, which may substantially improve the performance of in vitro EIT.